The Application of the Philosophical Thinking of “Three” From I Ching to Medical Education - Du, Yingjie; Zhang, Xinqing; Zhang, Jinjing; Wang, Guyan (Frontiers in Medicine, 2021)
Since ancient times, the Chinese have had a special understanding of the “Three”. Chinese philosophy originates from the I Ching, and the philosophical concept of “Three” is the core of the I Ching. The philosophical thinking about “Three” entails a complete dialectical thinking method that is consistent with the Western philosophical concept of “One Dividing into Three”. In this paper, we explain the philosophical concept of “Three” and suggest its application to medical education, including the learning and application of new technology, shared decision making between doctors and patients, and integration of medical humanities and medical science.